2022
DOI: 10.1038/s41586-022-04805-y
|View full text |Cite
|
Sign up to set email alerts
|

Communicating doctors’ consensus persistently increases COVID-19 vaccinations

Abstract: The reluctance of people to get vaccinated represents a fundamental challenge to containing the spread of deadly infectious diseases1,2, including COVID-19. Identifying misperceptions that can fuel vaccine hesitancy and creating effective communication strategies to overcome them are a global public health priority3–5. Medical doctors are a trusted source of advice about vaccinations6, but media reports may create an inaccurate impression that vaccine controversy is prevalent among doctors, even when a broad c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
83
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 32 publications
9
83
0
Order By: Relevance
“…In general, with regard to the uncertainty in parents' intentions to get their children vaccinated, the related question is who the relevant agent intervening with parents and providing clear and understandable information about vaccination should be. Trust in physicians could play an important role in improving communication and providing information to parents while still leaving them autonomy in making health decisions (Bartoš et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, with regard to the uncertainty in parents' intentions to get their children vaccinated, the related question is who the relevant agent intervening with parents and providing clear and understandable information about vaccination should be. Trust in physicians could play an important role in improving communication and providing information to parents while still leaving them autonomy in making health decisions (Bartoš et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of questioning the target group, effective provocation messages should lead to empowerment for fully informed child vaccination decisions (Masaryk & Hatoková, 2017). Another convincing way seems to be correcting people's misperceptions of facts about physicians' vaccination rates (Bartoš et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Most empirical studies use questionnaires to investigate the public attitude toward COVID-19 vaccines. Recently, a survey published in Nature [28] showed that, though doctors are usually considered as the authority in vaccination promotion, media reports give the false impression that there is widespread vaccine controversy in the doctor community. Enhancing consensus in this community can help improve the public trust level for vaccines.…”
Section: Vaccine Hesitancymentioning
confidence: 99%
“…It has been an important and necessary factor in the transfer of scientific knowledge, the management of uncertainty and fears, and the promotion of behaviour change during the Covid-19 pandemic (Finset et al, 2020;Melki et al, 2022). For example, experimental research revealed that the communication of doctors' consensus on trust in vaccination increased participants' Covid-19 vaccine uptake compared to a control group (Bartoš et al, 2022).…”
mentioning
confidence: 99%